The relationship between social support and mental health during the COVID-19 pandemic: a systematic review - Florentino Santisteban, Brian (2023)
The COVID-19 pandemic has affected the mental health of the population worldwide. Therefore, the present study aims to identify the methodological characteristics of the relationship between social support and mental health, through an analysis of the empirical evidence in research on adults during COVID-19 pandemic. The design used is a systematic review. Scopus and Web of Science electronic databases were used with articles published since 2020.A total of ten investigations were included, which reported the association between social support and mental health in adults from four continents. All of these investigations used non-probabilistic sampling, eight studies used the theoretical model of Zimet et al. (1988) for the evaluation of social support; in addition, variability was observed in the use of instruments for measuring mental health and social support. Likewise, nine investigations reported evidence of reliability of the instruments and none of validity. It is concluded that low levels of social support are significantly associated with greater symptoms of depression and anxiety during the COVID-19 pandemic. It is recommended to design intervention programs based on social support to decrease the negative impact on mental.health pf populations.